The spider family Dysderidae in the Balearic Islands - Bosmans, Robert; Lissner, Jørgen; Hernández-Corral, Jesús (Zootaxa, 2017)
The spider family Dysderidae in the Balearic Islands counts 6 species, which have all been revised. Dysdera arnedoi Lissner n. sp. and Parachtes riberai Bosmans n. sp. are newly described species from Majorca, where they seem to be confined. A neotype is designated for Dysdera balearica Thorell, 1873 and D. mordax L. Koch, 1882 is considered a junior synonym of the former. Dysdera lata Reuss, 1834 is cited for the first time in Majorca. Dysdera crocata C. L. Koch, 1838 and Harpactea dufouri (Thorell, 1873) occur on all the main Balearic Islands. Harpactea corticalis (Simon, 1882) and H. hombergi (Scopoli, 1763) were misidentified in the past and are deleted from the Balearic Islands list.